2015
DOI: 10.1038/jid.2014.383
|View full text |Cite
|
Sign up to set email alerts
|

Syk Mediates IL−17-Induced CCL20 Expression by Targeting Act1-Dependent K63-Linked Ubiquitination of TRAF6

Abstract: IL-17 has an important role in the immunopathogenesis of autoimmune diseases, and spleen tyrosine kinase (Syk) has been implicated as a critical molecule in the signaling pathways of various immunoreceptors. Chemokine (C-C motif) ligand 20 (CCL20) interacts with chemokine (C-C motif) receptor 6 to recruit IL-17-producing cells into the skin to promote progression of psoriasis. Herein we investigate how Syk regulates IL-17 signaling to affect CCL20 expression in primary human epidermal keratinocytes. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 53 publications
1
52
0
1
Order By: Relevance
“…Upon IL-17 stimulation, Syk associated with IL-17RA, Act1 and TRAF6, leading to activation of NF-κB [81]. Thus, there may be multiple avenues by which IL-17 activates NF-κB.…”
Section: Il-17 Signal Transductionmentioning
confidence: 99%
“…Upon IL-17 stimulation, Syk associated with IL-17RA, Act1 and TRAF6, leading to activation of NF-κB [81]. Thus, there may be multiple avenues by which IL-17 activates NF-κB.…”
Section: Il-17 Signal Transductionmentioning
confidence: 99%
“…TRAF3IP2 interacts with TRAF6 and is important for NF-κB activation downstream of IL-17 receptor signaling [64-66]. TRAF3IP2 is also important for CCL20 production from keratinocytes in response to IL-17 [67]. A coding alteration in TRAF3IP2 is associated with both psoriasis vulgaris and psoriatic arthritis.…”
Section: Innate Immunitymentioning
confidence: 99%
“…In addition, our immunohistochemical study showed high expression of phosphorylated Syk in psoriatic epidermis samples. Our recent study also revealed that Syk mediates IL-17A-induced signaling to regulate chemokine C-C motif ligand 20 (CCL20) expression in epidermal keratinocytes (Wu et al, 2015), implying potential roles of Syk inhibitors in the treatment of psoriasis. Additional studies are needed to determine the effects of diverse Syk inhibitors on the skin.…”
Section: Discussionmentioning
confidence: 83%